A new conjugate gradient algorithm for noise reduction in signal processing and image restoration - Huang, Pan; Liu, Kaiping (Frontiers in Physics, 2022)
Noise-reduction methods are an area of intensive research in signal processing. In this article, a new conjugate gradient method is proposed for noise reduction in signal processing and image restoration. The superiority of this method lies in its employment of the ideas of accelerated conjugate gradient methods in conjunction with a new adaptive method for choosing the step size. In this work, using some assumptions, the weak convergence of the designed method was established. As example applications, we implemented our method to solve signal-processing and image-restoration problems. The results of our numerical simulations demonstrate the effectiveness and superiority of the new approach.